STUDI PERATURAN MENTERI PENDAYAGUNAAN APARATUR NEGARA DAN REFORMASI BIROKRASI NOMOR 1 TAHUN 2015 TENTANG EVALUASI KINERJA PENYELENGGARA PELAYANAN PUBLIK DI BADAN PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL KOTA SALATIGA - Ratna Safitri; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Viewing from the reality that is happening in the bureaucracy in Indonesia, the image of public service which seems slow and cumbersome continues to be a particular concern in the bureaucratic reform program. It is closely linked to the conditions that occur in the service of licenses. BPPT and PM Salatiga is one of public service providers engaged in the licensing and investment sector. BPPT and PM Salatiga are apparently not capable to provide public services well. It is evidenced by the number of complaints from the public, not achieving the targets in the SPM, and there are still people who do not feel satisfied with the services provided. The purpose of this research is to describe the performance of public service providers in the BPPT and PM Salatiga and identify factors driving and inhibiting the performance of BPPT and PM Salatiga. This research uses descriptive type with qualitative approach. Data collection techniques used on this research is observation, interviews, documentation and triangulation. The results of this research indicate that the performance of public service providers in the BPPT and PM Salatiga is still needed to be increased. The indicators that are considered to be improved are the indicators of standard service, notice of service, complaint management and Public Service Information System (PSIS). Therefore, it is recommended to add training for employees, publish notice of service, provide a complaints management officer, implement the updating data and information related with the service held, and reactivate the website owned by BPPT and PM Salatiga.